Anxiety Sensitivity and Fast-Food Ordering Habits Among Black Adults - Vijay Nitturi; Tzu-An Chen; Michael J. Zvolensky; Lorna H. McNeill; Ezemenari M. Obasi; Lorraine R. Reitzel (New Prairie Press, 2021)
Black adults experience high rates of overweight/obesity, which is linked to chronic diseases and is exacerbated by fast-food consumption. Anxiety sensitivity, a relative stable fear of anxiety-related sensations, has been linked to high caloric intake. Here, we examine whether anxiety sensitivity is associated with fast-food ordering habits within a convenience sample of black adults. Of 124 adults (79.4% women; Mage = 49.3±11.6; 84.8% overweight/obese), 107 (86.3%) reported eating from a fast-food restaurant in the last month. Participants completed the Anxiety Sensitivity-Index 3, which has a total score and physical, cognitive, and social concerns subscales. Investigator-generated items queried frequency of ordering "supersized" quantities of fast-food (e.g., cheeseburgers, fries), and healthy items (e.g., salads, oatmeal, yogurt), respectively, from "never" to "always." Covariate-adjusted ordinal logistic regression models were used to assess relations between measures of interest. Anxiety sensitivity (total and physical concerns) was associated with greater odds of more frequently ordering supersized unhealthy fast-food; and anxiety sensitivity (total and cognitive concerns) was associated with lower odds of more frequently ordering healthy items from fast-food restaurants. Results suggest that adults with greater anxiety sensitivity may engage in fast-food ordering habits that can contribute to the overweight/obesity epidemic. Future studies should replicate results and determine the potential for anxiety sensitivity-reduction interventions to affect dietary choices that contribute to overweight/obesity.